Y is the output and x is the input. The given statement is output is 11 more than the output (x) so the function rule is y=x+11
Foils stands for first, outer, inner, last.
For example:
(3x + 5)(2x + 3)
Multiply the firsts together.
3x * 2x = 5x²
Now multiply the outer together.
3x * 3 = 9x
Now multiply the inners.
5 * 2x = 10x
Now multiply the lasts.
5 * 3 = 15
so the answer would be:
5x² + 9x + 10x + 15
5x² + 19x + 15
Hope this helps :)
I hope you understand my work goodluck :)
i give the answer here
Let's solve for x.<span><span><span>3x</span>−<span>4y</span></span>=3</span>Step 1: Add 4y to both sides.<span><span><span><span>3x</span>−<span>4y</span></span>+<span>4y</span></span>=<span>3+<span>4y</span></span></span><span><span>3x</span>=<span><span>4y</span>+3</span></span>Step 2: Divide both sides by 3.<span><span><span>3x</span>3</span>=<span><span><span>4y</span>+3</span>3</span></span><span>x=<span><span><span>43</span>y</span>+1</span></span>Answer:<span>x=<span><span><span>43</span>y</span>+<span>1</span></span></span>
Answer:
<u>18 in²</u>
Step-by-step explanation:
<u>Given :-</u>
height (h) = 12 in.
base (b) = 3 in.
<u>To Find :-</u>
Area
<u>Formulas Required :-</u>
Area (triangle) = 1/2bh
<u>Solving :-</u>
= 1/2 x 3 x 12
= 6 x 3
<u>Solution :-</u>
<u>18 in²</u>